The fate and behaviour of organic micropollutants during wastewater treatment processes: a review. (4th August 2014) - Meakins, N.C.; Bubb, J.M.; Lester, J.N.
The fate and behaviour of selected insecticides, herbicides, and polychlorinated biphenyls during primary sedimentation and secondary biological treatment of waste water are evaluated. The physico–chemical properties (chemical structure, aqueous solubility, octanol/water partition coefficient and Henry's Law constant) of these compounds which dictate the extent and mechanism of their removal from the waste water are assessed along with the effect of process operating conditions. The degree of organic micropollutant removal by adsorption onto solids, biological and chemical degradation or volatilisation determines their distribution and concentration in sewage sludges and final effluents. The implications of sludge disposal and sewage effluent discharges, containing persistent contaminants, to receiving environments is also discussed.